Kontribusi dan dampak Huntu Art Distrik dalam mengembangkan Ekowisata di Desa Huntu Selatan - I Ketut Suardana; I Wayan Suardana; Parta, I Wayan Seriyoga (Jurnal Senirupa Warna, 2025)
This study examines the contribution and impact of Huntu Art District in developing rural art-based ecotourism in Huntu Selatan Village, Bone Bolango Regency, using descriptive qualitative methods. Data were collected through observation, interviews, and literature studies. The results of the study indicate that Huntu Art District contributes and impacts the development of ecotourism as follows: 1) Contribution to products: Sustainable work programs and production facilities for rural art actors. 2) Contribution to distribution: Establishment of village markets, exhibitions, and marketing networks for community art and agricultural products. 3) Contribution to the environment: Environmental conservation activities and community empowerment in ecotourism. The resulting impacts include: 1) Impact on the arts: Increasing productive art actors and rural art-based artworks that support ecotourism. 2) Impact on the economy: Provision of a place for the community to market their crops. 3) Environmental impact: Support for environmental preservation by using organic materials and prohibiting non-organic materials. It is concluded that Huntu Art District plays an important role in the development of rural art-based ecotourism in South Huntu Village, so that the programs and efforts made need to be supported sustainably. Keywords: (Contibution; Impact; Ecoturism; Rural Art)